The Wendelstein Weak Lensing (WWL) pathfinder: accurate weak lensing masses for Planck clusters. Issue 1 (20th March 2019) - Rehmann, R L; Gruen, D; Seitz, S; Bender, R; Riffeser, A; Kluge, M; Goessl, C; Hopp, U; Mana, A; Ries, C; Schmidt, M
ABSTRACT: We present results from the Wendelstein Weak Lensing (WWL) pathfinder project, in which we have observed three intermediate-redshift Planck clusters of galaxies with the new 30 arcmin × 30 arcmin wide field imager at the 2 m Fraunhofer Telescope at Wendelstein Observatory. We investigate the presence of biases in our shear catalogues and estimate their impact on our weak lensing mass estimates. The overall calibration uncertainty depends on the cluster redshift and is below 8.1–16 per cent for z ≈ 0.27–0.77. It will decrease with improvements on the background sample selection and the multiplicative shear bias calibration. We present the first weak lensing mass estimates forPSZ1 G109.88+27.94 and PSZ1 G139.61+24.20, two Sunyaev-Zeldovich (SZ)-selected cluster candidates. Based on Wendelstein colours and SDSS (Sloan Digital Sky Survey) photometry, we find that the redshift ofPSZ1 G109.88+27.94 has to be corrected to z ≈ 0.77. We investigate the influence of line-of-sight structures on the weak lensing mass estimates and find upper limits for two groups in each of the fields ofPSZ1 G109.88+27.94 and PSZ1 G186.98+38.66. We compare our results to SZ and dynamical mass estimates from the literature, and in the case ofPSZ1 G186.98+38.66 to previous weak lensing mass estimates. We conclude that our pathfinder project demonstrates that weak lensing cluster masses can be accurately measured with the 2 m Fraunhofer Telescope.